Improving Students' Critical Thinking and Decision-Making Skills through a Problem-Based Learning (PBL) Model Assisted by a Vee Diagram - Deden Agustira; Rani Tania Pratiwi; Hendra Sumantri; Lanlan Muhria (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study is driven by the persistently low levels of students' critical thinking and decision-making skills, despite the implementation of various student-centered learning models such as Problem-Based Learning (PBL). Previous studies have focused mainly on PBL alone, with little attention to visual tools like the Vee diagram, which can enhance understanding and reasoning by helping students organize and reflect on information. However, the effectiveness of integrating the Vee diagram within the PBL framework in improving critical thinking and decision-making skills among high school students remains underexplored, indicating a research gap. This quasi-experimental study aims to evaluate the effectiveness of Vee diagram-assisted PBL compared to conventional PBL in enhancing students' critical thinking and decision-making skills. The study was conducted with 11th-grade science students at SMA Negeri 1 Lebakwangi, Kuningan. Data collection instruments included a critical thinking test (essay format), an observation sheet to assess decision-making skills, and a questionnaire to capture student perceptions of the PBL approach. Data were analyzed using the Independent Samples t-test. The results indicate that students taught using the Vee diagram-assisted PBL model demonstrated significantly greater improvement in critical thinking skills than those taught with conventional PBL. Decision-making skills were also higher in the Vee diagram-assisted PBL group. A positive and significant correlation was found between students' critical thinking and decision-making skills.